An assessment of coping mechanisms with poverty in Turkey after the 2008 global crisis: A study based on Turkey Welfare Monitoring Survey - Ergün, Buse. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
The thesis evaluates the variation among low income people's strategies for coping with poverty in Turkey after the 2008 global crisis and tries to understand the main factors and characteristic differences leading to variations in their decisions. According to Turkey Welfare Monitoring 1st Round (2009) results, low-income households reduced the use of health services, decreased food consumption and also reduced education expenditures. Besides, despite the limited coverage of social insurance in Turkey, poorest urban households do not have access to public safety net programs. They generally use their informal networks while dealing with poverty. In this context, the thesis summarizes descriptive statistics of urban poor characteristics and their reactions to income shocks. Probit estimations are used to determine the factors, such as wealth, household size, education level, employment status, number of children, being an immigrant etc., affecting coping mechanisms of low income people. In general, household size, wealth level of the family, employment status of the household head and social security ownership are found to be significant in Turkish poor urban household strategies to cope with poverty. Furthermore, the city where respondents of the survey reside determines the strategies of households. Household belongings, age, unemployment and speaking other language than Turkish inside the households appear to have strong effects on network choices. Private car ownership and number of children under age 15 are not found to be significant in any regressions.
Keywords: Public welfare -- Turkey.; Poverty -- Turkey.